Design disciplines and their potential connections for socially sustainable scenarios - Tiziana Ferrante (Techne, 2025)
The content of this Special Issue draws upon the scientific debate initiated during the “Beyond all Limits: International Conference on Sustainability in Architecture, Planning, and Design”, held in May 2022 at Vanvitelli University, Naples. The discussion focused on the latest international approaches to sustainability, as applied to the fields of planning, architecture, and design, and interpreted through the principles of the New European Bauhaus (NEB). Hence, focusing on novel design, operational and cultural strategies, aligned with the three pillars of the New European Bauhaus (NEB)-Sustainability, namely Aesthetics, Inclusion and a human-centred vision, can provide insights into rethinking the very meaning of sustainability, which is increasingly invoked while being at risk of becoming a mere slogan or rhetorical device. In the current context, the ecological transition and its social and cultural implications need to bridge the widening gap between institutional declarations and the everyday practices of citizens. This requires moving beyond a purely technical view of sustainability that lacks its ethical and social dimensions. The trajectory initiated with the “Beyond all Limits” Conference and continued in this Special Issue of TECHNE aims to investigate underexplored themes of sustainability, viewed as a cultural, social, and political act capable of renewing-through the experimental dimension of design disciplines-not only the forms of the built environment but also the deeper meaning of our contemporary living.